Lateral load response of large-diameter monopiles in sand. Issue 12 (24th September 2021) - Hu, Qian; Han, Fei; Prezzi, Monica; Salgado, Rodrigo; Zhao, Minghua
Abstract : Due to the increasing demand for renewable clean energy, there has been rapid growth in the development of offshore wind energy resources in recent years. The majority of offshore wind turbines are founded on single, large-diameter, open-ended pipe piles known as monopiles. The design of these piles is often done using the p – y method, which models the soil simply as non-linear springs placed along the pile length and assumes the pile to behave as a one-dimensional beam. To develop a design method that accounts for three-dimensional pile–soil interaction and that is applicable to general conditions, a series of finite-element (FE) analyses covering a wide range of pile dimensions, wall thicknesses, slenderness ratios, load eccentricities, sand types and sand relative densities were performed using an advanced sand constitutive model. In this paper, a set of equations is proposed that can be used to estimate the critical pile length, L crit (the pile length beyond which the pile lateral capacity no longer increases), the lateral capacity, H, and the lateral load–rotation curve for monopiles. The proposed method produces estimates of the lateral capacity of monopiles that are in very close agreement with those from the FE analyses.